Riqueza e distribuição de aves piscívoras em trecho urbano do Rio Uberabinha (Uberlândia, MG) - Moreira, Sandro Gonçalves (2005)
Waterbirds are an important functional group, responsible for countless ecological roles, including the dispersion of aquatic invertebrates. That group has been threatened by the processes of agricultural expansion and of urban growth, what promote degradation of natural habitats and environmental contamination, reﬂecting in the decrease of the richness of bird species. The present work was undertaken to evaluate aspects of the biology and ecology of piscivorous birds in an urban site of the Uberabinha river, municipality of Uberlândia, State of Minas Gerais. The study was conducted from January to December of 2004, having been registered ten species of birds (nine genders, four families and three orders). Among the observed birds, Phalacrocorax brasilianus presented the largest relative frequency and Pilherodius pileatus the smallest. Butorides striatus showed wider space distribution and Pilherodius pileatus, more restricted. There was not variation in the richness of species between stations (dry and rainy), and neither between the periods of the day (morning and evening). However, some species presented larger relative frequency in the rainy station (e.g. Nycticorax nycticorax) and other in the dry station (e. g. Egretta thula). Signiﬁcant variations were also registered in the frequencies of certain activities in relation to the seasons, for some of the investigated species (e.g. B. striatus feed more intensively in the dry station). We evidenced a preference of certain species by the use of native plants (trees and scrubs), mainly for nestling and/or rest. We concluded that the richness of piscivorous bird species is relatively high in the place, above all if the precarious conditions of environmental preservation be considered. Differences were observed in the relative frequency of the species forward of the year, as well as of the behaviors exhibited by the same ones in the exploration of the environment. The presence of the large sewer emissaries' and the amount of woody vegetables were the principal environmental variables correlated with the occurrence of birds in the study area.